Pengaruh Penerimaan Teknologi Keuangan Terhadap Niat Penggunaan E-Wallet Pada Mahasiswa di Surakarta dan Yogyakarta - Dwinanda Ripta Ramadhan; Muhammad Faiz Hardiansyah; Indria Desy Rachmawati (Universitas Teuku Umar, 2026)
The development of financial technology has driven the massive adoption of digital wallets (e-wallets), particularly among college students. Although e-wallets offer convenience and efficiency of transactions, their adoption is determined not only by the usability of the technology, but also by the perceived risk and individual characteristics of the user. This study aims to analyze the factors influencing e-wallet usage intentions by integrating the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), and adding the constructs of personal innovativeness and perceived risk in the context of fintech. This study used a quantitative approach with a survey method of 197 active college students who use e-wallets in the cities of Surakarta and Yogyakarta.. The results showed that facilitating conditions and perceived ease of use had a positive and significant effect on personal innovativeness, while perceived usefulness showed no significant effect. Furthermore, personal innovativeness and monetary risk were shown to have a positive and significant effect on behavioral intention to use e-wallets. These findings highlight the important role of individual innovativeness and socially influenced risk perceptions in shaping e-wallet adoption, particularly in emerging markets